2007
DOI: 10.1007/s11172-007-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Ligands of the colchicine site of tubulin: A common pharmacophore and new structural classes

Abstract: Structure-activity relationships for ligands of the colchicine site of tubulin were analyzed based on their common pharmacophore. The role of the elucidation of the three dimensional structure of the colchicine site of tubulin on the development of studies aimed at the search for the ligands of this site is analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Literature review revealed that there are at least three pharmacophore models for CBSIs. The first model consists of three hydrogen bond acceptors (Cysβ241, Leuβ252, Aspβ251, Alaβ250, and Valα181), one hydrogen bond donor (Thrα179), two hydrophobic centers, and one planar group . The second model is composed of one hydrogen bond acceptor (Asnα101), one hydrogen bond donor, one hydrophobic feature, and one aromatic ring feature while the third model is made up of three hydrogen bond acceptors (Valα181, Leuβ252, and Cysβ241), a hydrogen bond donor (Thrα179), and a hydrophobic skeleton with four hydrophobic centers .…”
Section: Resultsmentioning
confidence: 99%
“…Literature review revealed that there are at least three pharmacophore models for CBSIs. The first model consists of three hydrogen bond acceptors (Cysβ241, Leuβ252, Aspβ251, Alaβ250, and Valα181), one hydrogen bond donor (Thrα179), two hydrophobic centers, and one planar group . The second model is composed of one hydrogen bond acceptor (Asnα101), one hydrogen bond donor, one hydrophobic feature, and one aromatic ring feature while the third model is made up of three hydrogen bond acceptors (Valα181, Leuβ252, and Cysβ241), a hydrogen bond donor (Thrα179), and a hydrophobic skeleton with four hydrophobic centers .…”
Section: Resultsmentioning
confidence: 99%
“…[3,2-e] [1,2,4]triazolo [1,5-c]pyrimidines (7a and 7b); general procedure A few drops of triethylamine were added to a mixture of 5a or 5b (0.01mol) and the isonicotinic acid hydrazide (1.37 g, 0.01mol) in dioxane (30 mL). The reaction mixture was heated under reflux for 12 h then cooled and poured into ice-cold water.…”
Section: Synthesis Of Compounds (Rs)-n′-(ez)-(7-alkoxy-4-(4-chloro-phmentioning
confidence: 99%
“…(RS)-12-(4-Chlorophenyl)-9-methoxy-2-(pyridin-4-yl)-12H-chromeno [3,2-e] [1,2,4]triazolo [1,5-c] (RS)-12-(4-Chlorophenyl)-9-ethoxy-2-(pyridin-4-yl)-12Hchromeno [3,2e] [1,2,4] triazolo [1,5-c] …”
Section: Synthesis Of Compounds (Rs)-9-alkoxy-12-(4-chlorophenyl)-2-(mentioning
confidence: 99%
See 1 more Smart Citation
“…In the framework of our studies aimed at synthesizing compounds possessing antitumor activity we try to obtain bioisosteres of the antitumor drug Colchicine [1] on the basis of cage-like structures. The results of computer-assisted molecular modeling showed that compounds of the general formula I should quite effectively bind to tubulin which is a molecular target of Colchicine in vivo.…”
mentioning
confidence: 99%